Features of the Influence of Human Capital on Economic Development: The Case of Ukraine - Zolkover, Andrii; Kaplina, ?nastasi?a; Loboda, Olena; Kyrychenko, Natalia; Chopko, Nataliia (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The purpose of this article is to substantiate the nature of the relationship between the development of human capital (HC) and the development of the economy of Ukraine. Using the Granger test and cognitive modeling, the features of the development of HC in modern conditions and its influence on the country's economic development have been determined, and the dominant factors influencing the development and quality of HC have been empirically substantiated. The ambiguous nature of the influence of HC on the country's economy due to the inefficiency of spending in the field of education and health care has been established using the impulse modeling method. The positive impact of the development of HC on the development of the economy is leveled with the growth of investment in education and health care, which is due to the low efficiency of expenditures and the insufficient level of competence of state bodies.